SA-1 Conjunctivitis Treatment in Dog with Alkaline Water Eye Drop - A A S I Pradnyantari; A A N G D Wisesa; I W Y Semarariana; A A N O Pujawan; M P A Yunikawati; P T E Sucitrayani; P S Dwipartha; I N Suartha (Hemera Zoa, 2018)
Conjunctivitis is an inflammation of the conjunctival tissue that lines the eyelids and covers the sclera. The conjunctiva is the exposed mucous membrane and reacts to antigenic stimulation caused by contact with harmful stimuli. Handling of cases of conjunctivitis is generally treated with the administration of glucocorticoid antibiotics and topical antibiotics and broad spectrum (Ron, 2017). However, handling using Alkaline Eye Drop is still rare even never done especially in dogs. Alkaline Eye Drop is a liquid with an alkaline pH, the normal dog's eye pH is 8.05 (Billie et al, 2014). Alkaline water is easy to obtain and affordable. The use of Alkaline water to date has not been detected toxicity in the eye. But it is already used in humans to drink and cause antioxidant effects to the body (Rosa et al., 2012). It became the basis of the use of Alkaline Eye Drop for treatment in this case. The purpose of this paper is to get a more efficient, effective and without complications.